Penyuluhan Teknik Evaluasi Kinerja Melalui Pendekatan 5 Dimensi Kualitas Jasa/Servqual Di Sekolah Taman Kanak-Kanak Cikarang Selatan - Supriyati Supriyati; Adi Rusdi Widya; Siti Rahayu; Nisa Nurhidayanti; Ikhsan Romli (LPPI UMN AL WASHLIYAH, 2025)
This community service activity aims to improve the quality of educational services at Kindergarten Schools (TK) in South Cikarang through performance evaluation techniques based on the SERVQUAL method. The main problem identified was that there had been no systematic measurement of the quality of educational services at the school. The SERVQUAL method was used with five main dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Tangibles. The activity began with observations and interviews with the school to understand the initial conditions of the service. Furthermore, training and counseling were carried out for the school regarding the importance of performance evaluation and the use of questionnaires based on the five dimensions of service quality. The evaluation results showed a gap between parents' expectations and perceptions of the services provided. This gap is used as a basis for priority service improvements, especially in dimensions with the largest differences. This activity provides benefits for schools in improving and enhancing the quality of education in a sustainable manner and involving the active role of parents in the evaluation process